A Collaborative Parent–Teacher Design in CRT-Oriented Learning to Foster Independence in 4–5-Year-Old Children - Monica Ariningsari; Ida Dwijayanti; Arri Handayani (Universitas Pendidikan Ganesha, 2026)
Independence is an essential aspect of early childhood development that plays a significant role in fostering decision-making skills, responsibility, and the ability to complete tasks independently. However, the development of children's independence still faces several challenges, including the limited understanding of parents and teachers regarding Culturally Responsive Teaching (CRT)-oriented learning, the lack of structured collaborative strategies, and ineffective communication between home and school. This study aimed to develop a parent–teacher collaboration design within a CRT-oriented learning framework to enhance the independence of children aged 4–5 years. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The participants included children aged 4–5 years, teachers, and parents. Data were collected through observations, interviews, questionnaires, and documentation using children's independence assessment instruments and product validation sheets. Data were analyzed using descriptive quantitative and qualitative techniques through validity, practicality, and effectiveness testing. The findings revealed that the CRT-based parent–teacher collaboration guidebook met the criteria of being highly valid, practical, and effective in supporting the improvement of children's independence. The study concludes that CRT-based collaboration can serve as an effective strategy for fostering independence in early childhood. The implication of this study is the availability of a practical guide that can be utilized by teachers and parents to strengthen home–school partnerships in creating culturally responsive and child-centered learning environments.